Room temperature radiolytic synthesized Cu@CuAlO2-Al2O3 nanoparticles - Abedini, Alam; Saion, Elias; Larki, Farhad; Zakaria, Azmi; Noroozi, Monir; Soltani, Nayereh (MDPI AG, 2012)
Colloidal Cu@CuAlO2-Al2O3 bimetallic nanoparticles were prepared by a gamma irradiation method in an aqueous system in the presence of polyvinyl pyrrolidone (PVP) and isopropanol respectively as a colloidal stabilizer and scavenger of hydrogen and hydroxyl radicals. The gamma irradiation was carried out in a 60Co gamma source chamber with different doses up to 120 kGy. The formation of Cu@CuAlO2-Al2O3 nanoparticles was observed initially by the change in color of the colloidal samples from colorless to brown. Fourier transform infrared spectroscopy (FTIR) confirmed the presence of bonds between polymer chains and the metal surface at all radiation doses. Results of transmission electron microscopy (TEM), energy dispersive X-ray spectrometry (EDX), and X-ray diffraction (XRD) showed that Cu@CuAlO2-Al2O3 nanoparticles are in a core-shell structure. By controlling the absorbed dose and precursor concentration, nanoclusters with different particle sizes were obtained. The average particle diameter increased with increased precursor concentration and decreased with increased dose. This is due to the competition between nucleation, growth, and aggregation processes in the formation of nanoclusters during irradiation.